Alterações no fenômeno da coagulação na vigência do mastocitoma cutâneo em cães - Pinarel, Amanda Gullo [UNESP] (2015)
Mast cell tumor is characterized by neoplastic transformation of mast cells. This tumor is one of the malignancies that most often affect dogs. The clinical signs result from the release of granules contained in the cytoplasm of mast cells. When these granules are sensitized, it causes the production and release of several mediators from these beads (such as histamine, heparin, proteases and others). In neoplastic mast cells, these substances may be increased 25 to 50 times compared to a typical mast cell. Heparin forms a ternary complex with antithrombin III and inhibits the formation of thrombin, which may lead to an increase in clotting time. In this context, the aim of this study was to evaluate primary and secondary hemostasis of animals with mast cell tumor and correlate these findings with the tumor histological grade, using the Kiupel et al. (2011) classification for mast cell tumors. For this, were used 50 dogs, including 20 healthy animals (Control Group - GC) and 30 dogs with cutaneous mast cell tumors (Disease Group - GD) - those diagnosed by cytological and histopathological evaluation of the affected tissue. Among the GD dogs, was considered two subgroups of Kiupel classification: SK1 group, composed of 12 animals with high-grade mast cell tumor; SK2 group, consisting of 18 animals with low-grade mast cell tumor. To evaluate primary hemostasis, platelets were counted with an automatic counter immediately after collection of the blood sample. To evaluate secondary hemostasis, collected venous blood was used to determined fibrinogen values, prothrombin time (PT) and activated partial thromboplastin time (APTT) in coagulometer. Based on tumor grade, it was compared to the results of their respective clotting panels and then its correspondences were submitted to multivariate analysis. It was found that among the evaluated parameters, the APTT values were significantly higher in affected animals, particularly in high-grade ...